A REVIEW ON SUSTAINABLE TRANSPORT POLICY IN MALAYSIA - Zulazhar Abd Ghani; Muhammad Zaly Shah; Safizahanin Mokhtar, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Sustainable transport is an essential aspect of supporting urban mobility. The current percentage of urban population growth, with an estimated 75% of the population living in urban areas in Malaysia has led to increased travel demand. This population growth supported an increase in travel trips from 40 million trips in 2010. It is estimated to increase to 133 million trips in 2030. Based on the expected increase in Trips and CO2 emissions, the Government's priority is to provide consistent policies with the need for Global Sustainable Transport Policy. Therefore, this study will assess the interrelationship of global sustainable transport policies with the relevant national transport policies. This assessment will measure the translation level of global transportation policy to national policy. Therefore, using a Y shape matrix with seven criteria related to sustainable transport will be used to see the relevance of each policy. As a result, it was found that there is a relationship between global policy and national policy provided. The Five-Year Malaysia plan and National transport policy have translated the sustainable development goal policy and new urban agenda related to sustainable transport at most. However, the National Physical Plan also has a policy that covers almost all SDG and NUA policies. Overall, based on the global policy outlined by the United Nations and the national policy, the growing demand for trip development and analysis of the existing policy shows that the current transport policy focuses almost the same criteria as the global. Among the focus are road safety, transportation for all and sustainable infrastructure. These three criteria have highlighted most policy statements globally and nationally.